Choice of equipment and quality of life for people with stoma - Renata Florek; Renata Bajcarczyk; Dorota Kozieł (Kazimierz Wielki University, 2019)
The selection of stoma equipment is a highly individual matter for each patient. While taking care of the stoma patient, the nurse has a difficult task to overcome, which solution will make the patient feel comfortable. In the case of a correctly formed stoma, while maintaining the basic principles of stoma hygiene, care does not cause many difficulties. The most problematic is the concave stoma, in the abdominal fold and the convex stoma. The proper selection of equipment will prevent leakage and skin changes at a later stage. It will also improve the comfort and quality of life of people with a formed stoma. The nurse's role is to properly fit the equipment that will perfectly seal the stoma, prevent leakage, loosening of the stoma bag and make the patient not to rely on constant thinking about his or her illness